A quilt for Christmas : a Christmas novella [large type] - Carlson, Melody (Thorndike Press large print Christian fiction series., 2022)
"Christmas should be celebrated with family, but for Vera Swanson, that's not an option this year. Widowed and recently relocated, she is lonely in her condo-for-one--until little Fiona Albright knocks on her door needing help. With her mother seriously ill and her father out of town Fiona enlists Vera's aid, and when she finds out her new neighbor is a quilter, she has special request--a Christmas quilt for Mama. Vera will have to get a ragtag group of women together to fulfill the request. Between free-spirited artist Tasha, chatty empty nester Beverly, retired therapist Eleanor, and herself, Vera has hopes that Christmas for the Albright family will be merry after all. And she may even find herself a new family of friends along the way."--Publisher description.